Endometriosis – A Chameleon: Patientsʼ Perception of Clinical Symptoms, Treatment Strategies and Their Impact on Symptoms - Wimberger, P.; Grübling, N.; Riehn, A.; Furch, M.; Klengel, J.; Goeckenjan, M. (Geburtshilfe und Frauenheilkunde, 2014)
Introduction: Endometriosis is a chronic disease with differing clinical presentations. Treatment strategies depend mainly on clinical presentation and patient lifestyle. In women newly diagnosed with endometriosis, it is often difficult to understand the pathophysiologic origin, the potential individual impairment due to disease and the different treatment options. Compliance with the selected treatment is therefore often not optimal. Material and Methods: In a descriptive study, data of 51 women with endometriosis (mean age 36.2 years ± 11.3) were analyzed according to the predominant clinical presentation: asymptomatic disease, disease with typical symptoms, ovarian cysts or infertility. Results: More than 50 % of patients ascribed a therapeutic benefit to surgical intervention or endocrine treatment, especially women in the subgroup with dysmenorrhea who received combined treatment. It should be noted that in the group of women facing infertility, more than half stated that they could not decide on the value of diagnostic and therapeutic reproductive medicine. Nevertheless, more than half of the women in this group became pregnant within two years after the initial diagnosis. Discussion: When deciding on the best treatment strategy for endometriosis, it is important to take account of potential pain and infertility. Womenʼs perception of endometriosis will vary depending on their symptoms, the time of diagnosis and their lifestyle. Offering continuous information on clinical aspects and manifestations of the disease may improve treatment outcomes. Personalized counseling is an essential part of the clinical management of the disease.
Keywords: endometriosis; infertility; sterility; endocrine treatment; adenomyosis uteri interna; compliance